(untitled) (Journal of Economic Research & Business Administration, 2016)
In article modern problems on management of tax risks of the company, as integral part in the general system of adoption of administrative decisions are considered. The author proved need of the organization of scientific researches of use of various methods of decrease in tax risks at the enterprise, development of strategy of management of risk, in the form of forecasting of risks. Functions of tax risk are defined and measures for their account, for the purpose of decrease in tax risks are offered. The basic principles of an assessment of tax risks connected with the concept of the acceptable risk, determination of threshold values of risk, calculation of size of economic damage of the indicators necessary for a risk management are opened.